PENGEMBANGAN TANAMAN BAWANG MERAH DI DESA BULUPOUNTU JAYA KECAMATAN SIGI BIROMARU DI TINJAU DARI FAKTOR FAKTOR PRODUKSI - Hasmari Noer; Jumardin Jumardin; Indarti Widya Anggraeni (FAKULTAS PERTANIAN UNIVERSITAS ALKHAIRAAT, 2018)
This research aims to study and know the factors the production of red onion plant, has been implemented in Bulupountu Jaya, Sigi Biromaru, Sigi, Central Sulawesi. The results of this research is expected to be an information for the farmer about the factors that affect the production of red onion plant. The research was conducted from June to August 2016 in Bulupountu Jaya , Sigi Biromaru , Sigi , Central Sulawesi. Selection of the location of this research is based on that Bulupountu Jaya Village is the majority of red onion farmer. The method used is quantitative research method by survey and interviews to farmers red onion farming in Bulupountu.Location determination by purposive sampling and respondents by Multistage Random Sampling, through the stages : a.Specify the hamlet representing Bulupountu area, Specify farmer groups in each hamlet, c. Specify five respondents in each farmer groups, so there are 20 respondents. The results of this research indicate that the factors of land area, the amount of fertilizer, the number of seeds, the use of pesticides and pest control affect production in the development of onion farming in Bulupountu Jaya Village, Sigi Biromaru Subdistrict Sigi Regency Central Sulawesi Province